Strengthening the validity of international criminal tribunals - Nicholson, Joanna (Lawyer) (Brill E-Books, 2018)
International criminal law is experiencing a time of uncertainty and flux. There is increasing doubt surrounding where the international criminal justice project is heading. The contributions in this multi-disciplinary volume take stock of the situation and explore ways in which the validity of international criminal tribunals can be strengthened as the field of international criminal justice moves into a more uncertain future. Areas considered include: shaping the aims and aspirations of international criminal tribunals; increasing the effectiveness and legality of substantive international criminal law; improving certain processes and procedures of international criminal tribunals; improving relationships between international criminal tribunals and other organisations; and building trust between international criminal tribunals and African states.